Forest genetic resources conservation and management: overview, concepts and some systematic approaches: Vol. 1 - International Plant Genetic Resources Institute; Food and Agriculture Organization of the United Nations (2004)
This guide is the first volume in a series of three booklets that deals with the conservation of forest (tree and shrub) genetic resources. This volume gives an overview of concepts and systematic approaches to conservation and management of forest genetic resources. It outlines the need to conserve these resources and focuses on some of the strategies that may be employed in doing this. In addition, the volume focuses on planning national conservation of forest genetic resources, identification of research needs in forest resources, people's participation in the conservation of forest genetic diversity, and regional and international approaches to the conservation of forest genetic resources.